(untitled) (Philology, 2023)
This paper aims to present the communicative approach of task-based language teaching (TBLT) and the most significant contributions towards the definition and establishment of this methodology. After a brief overview on foreign language teaching, we will present the origins of the TBLT and its most prominent characteristics. We will go through the principles behind how language is conceived in this methodology and we will recover its main guidelines regarding course design (selection and sequencing of contents). In conclusions, we will present some of the limitations some authors point out in relation to this methodology, as well as its main advantages in language teaching.